Profile of elementary school students' numerical literacy ability - Astutik, Erna Puji; Purwasih, Silviana Maya (International Journal of Trends in Mathematics Education Research, 2023)
One of the impacts of the Covid-19 pandemic is the decline in numerical literacy skills due to learning loss. This study aims to describe the numerical literacy abilities of students at SDN Grogol and SDN Grabagan Sidoarjo. This research is quantitative descriptive research with a data collection technique in the form of a numerical literacy test based on the Minimum Competency Assessment (AKM) which is accessed on the Pusmenjar website with 20 questions in the form of complex multiple choice, multiple choice, matching and true false. Data analysis uses descriptive statistics which include the average of numerical literacy scors and the percentage of students who answered correctly for each indicator. Based on the research results, it can be concluded that the numerical literacy skills of students at SDN Grogol are in the medium category with an average score of 43.67. Meanwhile, the numerical literacy skills of students at SDN Grabagan are still low with an average score of 35.33. Furthermore, the answers to the numerical literacy test of students at SDN Grogol and SDN Grabagan have similarities in the indicator that most students answered correctly, namely indicator 7, understanding whole numbers which includes number symbols, the concept of place value, and generalization, 70% at SDN Grogol and 62% at SDN Grabagan. Meanwhile, the indicator that has the highest error is indicator 6, namely knowing the standard units of length/distance, weight and time with a percentage of students answering correctly of 30% at SDN Grogol and 23% at SDN Grabagan.